Navigating COVID-19 in Asia and the Pacific - Susantono, Bambang; Sawada, Yasuyuki 1967-; Park, Cyn-Young (Mandaluyong City, Metro Manila, Philippines Asian Development Bank, 2020)
This book gathers analysis and ideas to help policy makers tackle the impacts of the coronavirus disease (COVID-19) and build a more resilient and sustainable future.

COVID-19 has unleashed unparalleled challenges, yet provides opportunities to rethink strategies to tackle inequality, socioeconomic vulnerability, and environmental issues. This book collects contributions from ADB staff and experts to help inform policy on diverse themes. These include tackling the economic fallout, supporting SMEs, protecting the vulnerable, ensuring food security, and building resilient trade and supply chains. The authors highlight the importance of quality infrastructure, disaster risk management, digital acceleration, and regional cooperation in building back better together.
1. Economic Impact and Policy Response -- 2. Tackling the Financial Fallout -- 3. Supporting Micro, Small, and Medium-Sized Enterprises -- 4. Mitigating the Impact on the Poor and Vulnerable -- 5. Ensuring Food Security and Sustainable Agriculture -- 6. Building Resilient Trade and Supply Chains -- 7. Accelerating Digital Transformation -- 8. Rebooting Asia after COVID-19 -- 9 Building Back Better Together
Keywords: COVID-19 Pandemic, 2020 -- Economic aspects -- Pacific Area; COVID-19 Pandemic, 2020 -- Economic aspects -- Asia